Un modelo multifractal simplificado para flujos de tráfico autosimilares - Millán, Ginno (2018)
This paper proposes a new multifractal model, with the aim to provide a possible explanation to the locality phenomena to appear in the estimation of Hurst exponent in stationary second order temporal series, representing the self-similar traffic flows in high-speed computer networks. Analytically it is shown that this phenomenon occurs if the network flow consists of several components whit different Hurst exponents.